2015
DOI: 10.1155/2015/127828
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory and Apoptosis-Inducing Effects of Newcastle Disease Virus Strain AF2240 on Mammary Carcinoma Cell Line

Abstract: Breast cancer is the malignant tumour that developed from cells of the breast and is the first leading cause of cancer death among women worldwide. Surgery, radiotherapy, and chemotherapy are the available treatments for breast cancer, but these were reported to have side effects. Newcastle disease virus (NDV) known as Avian paramyxovirus type-1 (APMV1) belongs to the genus Avulavirus in a family Paramyxoviridae. NDV is shown to be a promising anticancer agent, killing tumour cells while sparing normal cells u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 38 publications
1
23
0
2
Order By: Relevance
“…NDV is known to cause inhibition of migration in various types of cancer cells 26,27 . However, the underlying mechanism is not well known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NDV is known to cause inhibition of migration in various types of cancer cells 26,27 . However, the underlying mechanism is not well known.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-1, -2, -7, -9 and -14 are well studied and known to be elevated in various cancer cells 24,25 . NDV mediated inhibition of cancer cell migration was reported in various cancer cells 26,27 . Although the studies are confined to MMP-2 and -9, its underlying molecular mechanism is not addressed.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a number of viruses may enhance host cell viability to prolong the release of virus particles ( 10 , 15 ). Recent studies revealed that apoptosis was induced in cultured and primary cells by some members of the family Paramyxiviridae such as Newcastle disease virus ( 16 , 17 ), Sendai virus ( 18 , 19 ), canine distemper virus ( 20 , 21 ), and peste des petits ruminants virus ( 22 ). The apoptotic mechanisms of these viruses were further evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The suppression of migration observed in this set-up was a direct effect of the reduction in cell proliferation due to apoptosis induction (Ahmad et al, 2015). …”
Section: Cell Death In Response To Ndv Infectionmentioning
confidence: 91%